Theory of the novel - Mazzoni, Guido, 1967- (Harvard University Press, 2017)
The novel is the most important form of Western art. It represents the totality of life; it is the flagship that literature lines up against systematic thought, against science and philosophy. Over the past two hundred years the novel has inspired more essays and reflections than any other aesthetic form, and contributed profoundly in conveying ideas of social life and patterns of behavior. Through the novel, Western literature expanded the range of its themes and possibilities, and has come to tell any story in any way; through the novel, Western literature has been able to delineate the ordinary existence of common people in a serious way, expressing the spirit of an age in which nothing matters except the single individual life. Nearly a century after the György Lukács' essay of the same name, this book offers a comprehensive interpretation of the novel as a cultural phenomenon and as a sign and symptom of the modern condition. This is a work of comparative literature covering four centuries of Western culture, but also a book about our epoch, about its values and its genealogy.--